Down-regulation of miR-199a-5p inhibits lipopolysaccharide- induced apoptosis of rat type Ⅱ alveolar epithelial cell line AECⅡ - WANG Wei, ZHAO Si-lin, FAN Fu-yuan, JIN Zhao-hui, LI Da, FU Yan (Jichu yixue yu linchuang, 2021)
Objective To investigate the expression of miR-199a-5p in the serum of patients with chronic obstructive pulmonary disease (COPD) and its effect on lipopolysaccharide (LPS)-induced apoptosis of rat type Ⅱ alveolar epithelial cells (AECⅡ) and possible mechanism. Methods Forty-five patients with COPD and 45 controls were enrolled in the first affiliated hospital of Hunan University of Traditional Chinese Medicine from April 2017 to December 2018 . AEC Ⅱ cells were cultured in vitro and were divided into control group , LPS group, anti-miR- 199a-5p+ LPS group, anti-miR-NC+LP group,anti-miR-199a-5p+si-FZD4+Lgroup and anti-miR-199a-5p+si-NC+LPS group. RT-qPCR was used to detect the expression of miR-199a-5p and FZD4 mRNA in serum and cells, flow cytometry was used to detect the apoptosis rate and Western blot was used to detect FZD4, B-lymphoma-2 (Bcl-2) and B-lymphoma-2 related proteins (Bax) in cells. The dual luciferase reporter gene experiment verified the targeting relationship between miR-199a-5p and FZD4. Results Compared with the control, the expression of miR-199a-5p in serum of COPD patients significantly increased (P＜0.05), and the expression of FZD4 mRNA significantly reduced (P＜0.05). Compared with the control group, the expression of miR-199a-5p in the LPS group significantly increased(P＜0.05), the mRNA and protein expression of FZD4 significantly reduced (P＜0.05), the apoptosis rate and the expression level of Bax protein significantly increased (P＜0.05), and the expression of Bcl-2 protein significantly reduced (P＜0.05). Compared with anti-miR-NC+LPS group, cell apoptosis and the expression of Bax protein in the anti-miR-199a-5p+LPS group significantly reduced (P＜0.05), while the expression of Bcl-2 protein significantly increased (P＜ 0.05). There was no significant change in the detection indexes between the LPS group and the anti-miR-NC+LPS group (P＞0.05). miR-199a-5p targets FZD4, compared with anti-miR-199a-5p+si-NC+LPS group, cell apoptosis rate and the expression level of Bax protein in the anti-miR-199a-5p+ si-FZD4+LPS group all significantly increased (P＜0.05), while the expression of Bcl-2 protein significantly reduced (P＜0.05). Conclusions The expression of miR-199a-5p is increased in serum of COPD patients and in LPS-induced AECⅡcells. Down-regulating miR-199a-5p expression may inhibit LPS-induced AECⅡ cell apoptosis by up-regulating FZD4 expression.